Macrophages induce gingival destruction via Piezo1-mediated MMPs-degrading collagens in periodontitis - Zhao, Tong; Chu, Zhuangzhuang; Chu, Catherine Huihan; Dong, Shuo; Li, Guoqing; Wu, Jin; Tang, Chunbo (Frontiers in Immunology, 2023)
Macrophages are an integral part of the innate immune response in periodontal tissue and play a crucial role in the progression of periodontitis. Here we reported that macrophages also provoke periodontitis-induced gingival recession through Piezo1-mediated collagen degradation. We discovered that the PIEZO1 expression was markedly elevated in patients with periodontitis through transcriptomic profiling. Moreover, Piezo1 promoted macrophage polarization toward the M1 type in response to lipopolysaccharide (LPS) and induced production of pro-inflammatory cytokines, which in turn stimulated production of matrix metalloproteinases (MMPs) leading to collagen degradation. Our study suggests that Piezo1 might be a potential therapeutic target for treating periodontitis-induced gingival recession.